2018
DOI: 10.4049/immunohorizons.1700038
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and IgG Subclass of Antibodies Elicited by Targeted DNA Vaccines Are Influenced by Specificity for APC Surface Molecules

Abstract: Upon APC-targeted DNA vaccination, transfected cells secrete fusion proteins with targeting units specific for surface molecules on APC. In this study, we have tested several different targeting units for their ability to influence the magnitude and subclass of Ab responses to hemagglutinin from influenza A virus. The experiments employed bivalent homodimeric Ig-based molecules (vaccibodies). The overall efficiency in BALB/c mice depended on the targeting units in the following order: αMHC class II > αC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 60 publications
4
58
1
Order By: Relevance
“…Our side-by-side analysis of nine different APC targets for vaccines has demonstrated that MHCII-targeting was the most efficient for induction of antibodies. 17 This result is in agreement with our previous studies demonstrating that MHCII-targeted antigen could induce protective antibody responses, both in mice 10 and larger animals. 18 In mice, MHCII-targeted hemagglutinin (HA) induced complete antibody-mediated protection within 8 days against challenge with influenza virus, and protective immunity was maintained for at least 10 months.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our side-by-side analysis of nine different APC targets for vaccines has demonstrated that MHCII-targeting was the most efficient for induction of antibodies. 17 This result is in agreement with our previous studies demonstrating that MHCII-targeted antigen could induce protective antibody responses, both in mice 10 and larger animals. 18 In mice, MHCII-targeted hemagglutinin (HA) induced complete antibody-mediated protection within 8 days against challenge with influenza virus, and protective immunity was maintained for at least 10 months.…”
Section: Introductionsupporting
confidence: 93%
“…DNA vaccines encoding fusion proteins that target antigens to MHC class II molecules elicit increased antibody responses. 10,1719 To understand the mechanistic basis for these observations, we have here studied vaccine proteins in models with traceable T and B cells of known specificity. Protein delivery was chosen over DNA vaccination since the dose of administered protein could then be directly controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Another type-2 adjuvant, Alum, is also an effective adjuvant for the influenza SV vaccine ( 41 ). In contrast, previous studies indicated that antibody-mediated responses such as antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) via Th1-related antibodies are also important for the elimination of influenza virus ( 16 19 ). Indeed, CpG-ODN is reported to enhance vaccine-induced type-1 (Th1) immune responses and protect the mice from lethal viral infections such as influenza ( 42 , 43 ).…”
Section: Resultsmentioning
confidence: 89%
“…HP-β-CyD and K3 CpG-ODN-adjuvanted influenza SV protected against challenge with a high dose of influenza virus, which the single adjuvant vaccines could not protect against (Figure 2 ), suggesting that the anti-viral immune response generated by this combination of adjuvants is very strong. Notably, this adjuvant combination greatly induced IgG2c production, which is reported to be correlated with anti-viral immunity including ADCC and CDC ( 15 19 ). In contrast, the production of IgE by the combined adjuvant was lower than that of HP-β-CyD alone, and the biocompatibility of these adjuvants is expected to be high because they have already been used in the clinic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation